BYSTANDER INTERVENTION AMONG DRINKING GAMERS Bystander Intervention Among College Student Drinking Gamers: Sexual Assault Attitudes, Self-Efficacy, and Intent to Intervene - Pazienza, Rena (Journal of interpersonal violence, 2022)
Heavy drinking and sexual assault warrant significant concern on U.S. college campuses as emerging evidence suggests that the risk for sexual victimization is amplified in the context of high-risk drinking behavior. Despite recent attention to sexual assault (e.g., MeToo Movement), rates of perpetration remain largely unchanged. In applying the bystander intervention framework, our understanding of the relation between key factors that may facilitate or prevent behavioral action, or when and how these factors are most salient, is limited. The present study examined whether bystander attitudes and bystander self-efficacy interact to predict bystander intent to intervene. Hypotheses were tested among college student drinking gamers, a group at particular risk for involvement in situations of sexual violence. Participants (N = 964) were traditional college-aged student drinking gamers recruited from three universities across the East and Southern Central United States. After controlling for Greek affiliation, prior intervention training and social desirability, hypotheses were partially supported. Higher rape supportive attitudes (rape myth acceptance) were negatively associated with bystander intent to intervene across all participants, but bystander self-efficacy significantly moderated the relation between bystander attitudes (rape myth acceptance) and bystander intent to intervene only among women college student drinking gamers. The interaction effect was not significant among men. For all participants, there was a significant relation between bystander self-efficacy and bystander intent to intervene such that as self-efficacy increases, bystander intent to intervene increases. The discussion addresses implications for sexual assault prevention programs on college campuses and directions for future research.